Pathology of Legal and Executive Obstacles of Securitization of Banks' Facility Assets from Jurisprudential and Economic Points of View - Hossien Harorani; Seyed Hadi Arabi; Abbas Arabmazar (تحقیقات مالی اسلامی (پیوسته), 2022)
The purpose of this article is to list the legal, jurisprudential and executive obstacles and challenges of securitization of bank facility assets, and by using the normative and descriptive-analytical methods, some solutions will be proposed to extend the use of this tool. The findings show that despite the serious need of banks to increase their ability to provide facilities, there are some challenges such as the high cost of issuing securities, the pricing of claims regardless of market conditions (financial repression) and the higher profits of other parallel markets compared to the earnings of these securities, prolonged examination  process and complex structure of securitization, the suspension of the use of this tool due to the 2008 financial crisis, the high credit risk of borrowers and the low quality of bank assets, the existence of six jurisprudential theories about sale and the lack of consensus among jurists in this context, legal and regulatory gap in the establishment of corporate governance in banks, and the non-applicability of the tax laws of partnership bonds to securities resulting from bank claims, which all lead to a decrease in investors’ motivation to buy these bonds on the one hand and a decrease in the willingness of banks to securitize claims, on the other. The consequences of not paying attention to this matter will appear in the reduction of banks' financing power, which will in turn decrease their capital adequacy ratio.